Encyclopedia of knowledge management - Schwartz, David G. 1963-; Te'eni, Dov (Information Science Reference, 2011)
"This two-volume collection covers all aspects of knowledge management, which range from knowledge identification and representation, to the impact of knowledge management systems on organizational culture, to the significant integration and cost issues being faced by human resources, MIS/IT, and production departments" - Provided by publisher
Includes bibliographical references
Keywords: Knowledge management; Information resources management; Information networks / Management; Organizational learning; Organisation; American dream; Einkommensverteilung; Wissensmanagement; USA; Aufsatzsammlung; Wörterbuch